2022
DOI: 10.1021/acs.nanolett.1c04764
|View full text |Cite
|
Sign up to set email alerts
|

Optical Bound States in the Continuum Enabled by Magnetic Resonances Coupled to a Mirror

Abstract: Dielectric metasurfaces made of high refractive index and low optical loss materials have emerged as promising platforms to achieve high-quality factor modes enabling strong light–matter interaction. Bound states in the continuum have shown potential to demonstrate narrow spectral resonances but often require asymmetric geometry and typically feature strong polarization dependence, complicating fabrication and limiting practical applications. We introduce a novel approach for designing high-quality bound state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…45−47 In comparison, less attention has been paid to dielectric-metal hybrid nanostructures owing to the Ohmic loss of metals, which may influence the quality factors of BICs. 33,48 Recent studies reveal that two types of BICs with quality factors as large as ∼800 can also be realized in dielectric-metal hybrid nanostructures by exploiting the surface plasmon polaritons (SPPs) generated on the surfaces of metal films. 49 Considering the spectrum match between the optical mode and the excitation light (e.g., femtosecond laser pulses), BICs with quality factors of ∼100 are sufficient to dramatically enhance the nonlinear optical absorption of Si nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…45−47 In comparison, less attention has been paid to dielectric-metal hybrid nanostructures owing to the Ohmic loss of metals, which may influence the quality factors of BICs. 33,48 Recent studies reveal that two types of BICs with quality factors as large as ∼800 can also be realized in dielectric-metal hybrid nanostructures by exploiting the surface plasmon polaritons (SPPs) generated on the surfaces of metal films. 49 Considering the spectrum match between the optical mode and the excitation light (e.g., femtosecond laser pulses), BICs with quality factors of ∼100 are sufficient to dramatically enhance the nonlinear optical absorption of Si nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Auger effect, which is proportional to the cubic of the carrier density, plays a crucial role in this scenario . By placing Si nanoparticles on a thin metal film, it was demonstrated very recently that the quantum efficiency can be further improved to ∼6.0–8.0% by exploiting the strongly localized electric field and dramatically reduced linewidth provided by the so-called mirror-image-induced magnetic dipole (MMD) resonance. , In addition, the good thermal conductivity of the metal film enables the stable emission of white light for a long time. It was shown that surface lattice resonances with quality factors larger than those of the MMD resonance can be achieved in a regular array of Si nanopillars, which offers a larger nonlinear optical absorption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Mie resonant frequencies in these cases are influenced by various factors including material property, structure, and resonance mode and exhibit a complex variation with the gap size between dielectric particle and metallic substrate, which still needs a comprehensive mechanism interpretation. For example, the hybrid MD resonant wavelength of Si nanorod on Ag substrate demonstrates a blue shift as the gap size increases [ 21 ], while for the case of Si nanorod on Au substrate, the resonant wavelength is blue-shifted with the decrease of thin film thickness [ 23 ]. In addition, some researches demonstrate that the MD resonant wavelength is hardly changed or slightly red-shifted when Si nanosphere is away from metallic substrate [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to figure out the dependency relationship between resonant frequency and their gap size. Such a frequency shift will sharply degrade the performance of many optical devices designed at specific wavelength, such as nonlinear optics [ 23 , 24 , 26 ] and reflection-type metasurfaces [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%